High toluene exposure risk increases risk of olfactory dysfunction in furniture workers - Magdalena Wartono; Herkutanto Herkutanto; Niken Lestari (Universa Medicina, 2015)
BACKGROUNDFew studies have investigated the impact on olfactory functioning ofoccupational exposure to toluene, an industrial solvent used in paints andcleaning fluids. The estimated olfactory dysfunction prevalence is 0.5–5%. Patients frequently do not complain about olfactory dysfunction.However, occupational exposure to chemicals may affect workers’ healthand safety, because of their continuous inhalation. This study aimed toexamine the relationship between toluene exposure and olfactorydysfunction in furniture workers.METHODSThis was a cross-sectional study involving 65 workers. Data collectionwas by observation and interview on demographic characteristics, historyof habits, and symptoms of chronic rhinitis. Risk of exposure scores wereevaluated from potential hazard, exposure level, duration of employment,type of work, use of masks, ventilation of work space, and education andtraining. Olfactory function was tested using Sniffin’ Sticks, anddetermination of environmental toluene level was by personal sampling.The odds ratio was used to test correlations between variables.RESULTSOnly 44 subjects could be analyzed, 37 (84.1%) of whom had olfactorydysfunction. Workers with high toluene exposure had a significantly 12.5-fold risk of olfactory dysfunction in comparison with those with lowexposure (OR=12.5; CI 95% 1.35 – 115.79).CONCLUSIONSToluene exposure increases risk of olfactory dysfunction in furnitureworkers. Olfactory function testing should be considered for initialscreening or periodic testing of furniture workers. Low toluene levels witha high proportion of olfactory dysfunction indicate that olfactory dysfunctionis an early negative impact of chemical inhalation.